1987
DOI: 10.1128/jcm.25.4.751-753.1987
|View full text |Cite
|
Sign up to set email alerts
|

Application of whole-cell DNA restriction endonuclease profiles to the epidemiology of Clostridium difficile-induced diarrhea

Abstract: Two patients in one hospital room acquired pseudomembranous colitis, one shortly after the other. The DNA restriction patterns of isolates from the patients and of four isolates from the environment were indistinguishable from one another and differed from isolates of other patients. Restriction endonuclease digest analysis appears to be a useful method for studying the epidemiology of Clostridium difficile. Clostridium difficile is now well recognized as the etiologic agent of pseudomembranous colitis (PMC) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Different methods have been developed to study the epidemiology of C. difficile or to identify or type strains. Analysis of restriction patterns of DNA of clinical isolates has been used for investigations of epidemiology and typing of C. difficileassociated diarrhea (24). Pantosti et al (37) used the electrophoretic patterns of extracted proteins to characterize C. difficile strains from various sources and showed correlation between certain electrophoretic patterns and virulence.…”
Section: Discussionmentioning
confidence: 99%
“…Different methods have been developed to study the epidemiology of C. difficile or to identify or type strains. Analysis of restriction patterns of DNA of clinical isolates has been used for investigations of epidemiology and typing of C. difficileassociated diarrhea (24). Pantosti et al (37) used the electrophoretic patterns of extracted proteins to characterize C. difficile strains from various sources and showed correlation between certain electrophoretic patterns and virulence.…”
Section: Discussionmentioning
confidence: 99%
“…This bacterium is considered to be the main agent of nosocomially acquired diarrhea among adults [2]. Many various typing methods have been developed to investigate nosocomial outbreaks of C. di¤cile, some based on phenotype (lysotyping [3], serogroup-ing [4], SDS-PAGE [5], immunoblotting [6]) and others on genotype (plasmids [7], REA [8], ribotyping [9], PFGE [10], RAPD [11]). Recently, Kostman et al developed a method of PCR-ribotyping that was shown to be reproducible, easy to perform and cost-e¡ective [12].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the utility of DNA fingerprinting for epidemiological analysis of phenotypically indistinguishable microbial pathogens (1,4,15,18,19,22,36,(38)(39)(40). Ribotyping, based on restriction fragment length polymorphisms in the chromosomal DNA containing rRNA genes, has also been used as a means of detecting interspecies and interstrain differences (13,14,24).…”
mentioning
confidence: 99%